2019
DOI: 10.1073/pnas.1816391116
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating cancer metabolic plasticity by coupling gene regulation with metabolic pathways

Abstract: Metabolic plasticity enables cancer cells to switch their metabolism phenotypes between glycolysis and oxidative phosphorylation (OXPHOS) during tumorigenesis and metastasis. However, it is still largely unknown how cancer cells orchestrate gene regulation to balance their glycolysis and OXPHOS activities. Previously, by modeling the gene regulation of cancer metabolism we have reported that cancer cells can acquire a stable hybrid metabolic state in which both glycolysis and OXPHOS can be used. Here, to compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
251
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(265 citation statements)
references
References 58 publications
13
251
0
1
Order By: Relevance
“…Further studies are required to ascertain the species of ROS that have detrimental effects on melanoma cells. One could imagine this could be cell-line or tumor specific, as gene regulatory network (GRN) has been linked with the ability of cells to undergo metabolic plasticity (Jia et al, 2019;Paudel and Quaranta, 2019) . Future work seems necessary to also investigate the compensatory antioxidant pathways, and how they help maintain redox homeostasis in melanoma cells (Harris et al, 2015) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are required to ascertain the species of ROS that have detrimental effects on melanoma cells. One could imagine this could be cell-line or tumor specific, as gene regulatory network (GRN) has been linked with the ability of cells to undergo metabolic plasticity (Jia et al, 2019;Paudel and Quaranta, 2019) . Future work seems necessary to also investigate the compensatory antioxidant pathways, and how they help maintain redox homeostasis in melanoma cells (Harris et al, 2015) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cancer cells can utilize glycolysis, mitochondrial respiration, or both, depending on their environment (Dang, 2012) . Furthermore, cancer cells can adapt metabolically in response to external perturbations (DeBerardinis et al, 2008;Jia et al, 2019) . This metabolic flexibility provides cancer cells with energy, and necessary intermediates for biosynthetic processes required for survival and to maintain redox balance under changing environments (DeBerardinis et al, 2008;Paudel and Quaranta, 2019) .…”
mentioning
confidence: 99%
“…Here, we report that the SKMEL5 melanoma cells can indeed repress both their glycolysis and OXPHOS activity when they transition into the idling state as a response to therapy. Furthermore, using the RNA-sequencing (RNA-Seq) data of human melanoma M397 and M229 cell lines and melanoma patient samples from from Gene Expression Omnibus (GEO), we show that melanoma cells consistently decrease their glycolysis and/or OXPHOS activity and exhibit a convergence toward the L/L phenotype upon long-term MAPKi treatment, as characterized by the AMPK/HIF-1 signatures (15) and the metabolic pathway scores (3). The residual melanoma tumors may be composed of a significant fraction of drug-tolerant idling cells.…”
Section: )mentioning
confidence: 98%
“…To elucidate metabolic plasticity in cancer, we established a modeling framework that couples gene regulation with metabolic pathways (Supplementary Fig. S1) (3). Our modeling analysis demonstrates a direct association of the master gene regulators of cancer metabolism AMPactivated protein kinase (AMPK) and hypoxia-inducible factor (HIF)-1 with three major metabolic pathways -glycolysis, glucose oxidation and fatty acid oxidation (FAO).…”
Section: )mentioning
confidence: 99%
“…In another study, [U‐13C]‐glucose or [U‐13C]‐glutamine by NMR analysis recognized differentiation mechanisms of that Luminal A and triple‐negative. breast cancer with differential expression of hormonal receptors exhibited different utilization of energy . O'day (2018) performed unbiased nuclear magnetic resonance spectroscopy screening to identify altered bioenergetics in metastatic cancer.…”
Section: Introductionmentioning
confidence: 99%